The Effect of Cholesterol on Membrane Dynamics on Different Timescales in Lipid Bilayers from Fast Field‐Cycling NMR Relaxometry Studies of Unilamellar Vesicles. Issue 3 (31st January 2014) - Fraenza, Carla C.; Meledandri, Carla J.; Anoardo, Esteban; Brougham, Dermot F.
Abstract The general applicability of fast field‐cycling nuclear magnetic resonance relaxometry in the study of dynamics in lipid bilayers is demonstrated through analysis of binary unilamellar liposomes composed of 1, 2‐dioleoyl‐sn‐glycero‐3‐posphocholine (DOPC) and cholesterol. We extend an evidence‐based method to simulating the NMR relaxation response, previously validated for single‐component membranes, to evaluate the effect of the sterol molecule on local ordering and dynamics over multiple timescales. The relaxometric results are found to be most consistent with the partitioning of the lipid molecules into affected and unaffected portions, rather than a single averaged phase. Our analysis suggests that up to 25 mol %, each cholesterol molecule orders three DOPC molecules, providing experimental backup to the findings of many molecular dynamics studies. A methodology is established for studying dynamics on multiple timescales in unilamellar membranes of more complex compositions.